Effects of Cigarette Butt Leachate on the Growth of White Mustard (Sinapis alba L.) and Soil Properties: A Preliminary Study - Sinazo Ajibade; Barbara Simon; Anita Takács; Miklós Gulyás (Pollutants)
Cigarette butts (CBs) are emerging soil contaminants, releasing chemicals upon contact with moisture. This study examined heavy metal concentrations leached from smoked and unsmoked CBs (Pall Mall, Philip Morris, and Marlboro) into OECD artificial soil and Vertisol soil and their accumulation in white mustard (Sinapis alba L.). Key physiological parameters, including germination rate, plant height, fresh weight, and dry weight, were analyzed, along with the uptake of heavy metals (Al, Fe, Mn, Zn, Ba, Ti, and Cu) and essential elements (Ca, Mg, Na, and K). Results showed that Mn had the highest bioaccumulation index (BAI = 1.10) in OECD soil, while Zn uptake was consistently high across soil types. Soil type significantly influenced plant height (χ2 = 41.269, p < 0.01) and elemental composition, with Vertisol soil facilitating greater overall growth and heavy metal uptake than OECD soil. MANOVA revealed no three-way interaction among soil type, CB use, and CB brand on elemental uptake. However, two-way interactions, particularly between soil type and CB use (F (4, 39) = 40.233, p < 0.001, Wilk’Λ = 0.195), showed significant effects on heavy metal uptake. These findings highlight the complex interactions influencing plant contamination, underlining the ecological risks of CB pollution in soils.